2016
DOI: 10.4995/wrs.2016.3917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet supplementation with live yeast (Saccharomyces cerevisiae) on performance of rabbit does and their progenies

Abstract: A study was conducted to determine the effect of live yeast supplementation in the diet of rabbit does on their mortality and reproductive performance and the performance of their progeny. A total of 52 cross-bred rabbit does (New Zealand×Californian) were divided into 2 groups differing in diet offered during 2 reproductive cycles and containing (group S; n=26) or not (group C; n=26) 1 g of yeast (Actisaf Sc 47, S.I. LESAFFRE, France)/kg of feed. Natural mating was performed 11 d after kindling and kits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Parallel to the current ndings, Ayyat et al, (1996) suggested that diets supplemented live yeast (Lacto-Sacc) for lactating rabbits increased milk production, litter size, and weight at weaning. Furthermore, Belhassen et al, (2016) showed that the fertility rate and the viability rate of litter at birth of rabbit does were higher in the live yeast (probiotic) group than those with the control diet.…”
Section: Productive Performance Of Does and Offspring During Lactationmentioning
confidence: 99%
“…Parallel to the current ndings, Ayyat et al, (1996) suggested that diets supplemented live yeast (Lacto-Sacc) for lactating rabbits increased milk production, litter size, and weight at weaning. Furthermore, Belhassen et al, (2016) showed that the fertility rate and the viability rate of litter at birth of rabbit does were higher in the live yeast (probiotic) group than those with the control diet.…”
Section: Productive Performance Of Does and Offspring During Lactationmentioning
confidence: 99%